Appendix 4.2: Confidential Cable from the US Embassy in Manila, “Supreme Court Justice Calls for Lifting of Martial Law,” 7 July 1976 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Widely known as the “Great Dissenter,” this cable shows Justice Claudio Teehankee Sr.’s ability to counter Marcos with the latter’s legalistic finesse, i.e., by stating that mere advocacy of the lifting of martial law was legally permissible since the president himself declared that it was only a temporary necessity. Ambassador William H. Sullivan noted that Teehankee was “somewhat nervous” when asked about his “activist” stance, which suggests that in 1976, Justice Teehankee knew how to confine his opposition to martial rule within the bounds of the law. Justice Antonio Barredo, meanwhile, is portrayed in this cable as someone who considers himself privy to president Marcos’s thoughts, or in any case fully trusts the wisdom of the president.